Irradiation effect on in vitro organogenesis, callus growth and plantlet development of Gerbera jamesonii - Hasbullah, N.A.; Taha, R.M.; Saleh, A.; Mahmad, N. (2012)
The present work was carried out to study the effects of gamma irradiation on in vitro growth of explants, callus and the formation of shoots and plantlets. Irradiation is known to exhibit or inhibit the differentiation of cells and growth of plants in vitro, which helps in producing new plant varieties. Gamma irradiation is one of the physical mutagens that are widely used for mutation breeding. A gradual decline was observed in the number of shoots regenerated from irradiated petiole explants compared to control. Numbers of shoots regenerated from irradiated petiole explant cultured on Murashige & Skoog medium supplemented with 2.0 mg L-1 BAP and 0.5 mg L-1 NAA was reduced to 6.6 +/- 0.9 from 7.5 +/- 0.4 (control) when explants were exposed to 20 Gray of irradiation dose. Similar observation was reported on effects of gamma irradiation on in vitro propagated plantlets. Gradual decline was observed based on plant height as the dose of gamma irradiation increased. A significant decline was observed in the fresh weight of irradiated callus compared to control. In this case, growth responses of callus were strongly influenced by the radiation dose. The fresh weight of callus was reduced to 76.4 +/- 2.2 compared to 89.7 +/- 0.5 of control when callus tissues were exposed to 20 Gy.